Pattern of Adolescents Happines in Islamic Boarding Schools: Examine The Role of Self Acceptance and Prosocial Behavior - Muhamad Ulul Albab; Amherstia Pasca Rina (Jurnal Psikologi Teori dan Terapan, 2023)
This study aims to determine the relationship between self-acceptance and prosocial behavior with happiness in adolescents at the Assalafi Al Fithrah Islamic boarding school Surabaya. This study used quantitative research with a total of 150 subjects. The sampling technique in this study is a random sampling technique. The research sample included in this study was adolescents aged 12-18 years who lived in the one of Islamic boarding school in Surabaya with 73 male and 77 female subject. Based on the calculation of the results of the analysis using Multiple Linear Regression Analysis, a correlation score of 0.772 was obtained with a significance of p = 0.000 (p < 0.05) which means that there is a relationship between self- acceptance  and  prosocial  behavior  with  happiness.  Meanwhile,  a correlation score of 0.507  was obtained  with  a  significance  of 0.000  (p<0.05)  which  means  that  there  is  a  positive relationship between self-acceptance and  happiness. The correlation score of prosocial behavior with happiness was 0.487 with a significance of 0.000 (p<0.05). As a result, the higher the self-acceptance and prosocial behavior possessed by adolescents, the higher the level of happiness they feel. The effective contribution in this study was 0.487, which means  that  self-acceptance  and  prosocial  behavior  have  an  influence  of  48.7%  on happiness. ABSTRAK Penelitian ini bertujuan untuk  mengetahui  hubungan  penerimaan diri dan perilaku prososial dengan kebahagiaan pada remaja di pondok pesantren Assalafi Al Fithrah Surabaya. Penelitian ini menggunakan penelitian kuantitatif dengan jumlah 150 subyek. Teknik penarikan sampel dalam penelitian ini adalah teknik random sampling. Sampel penelitian yang diturut sertakan dalam penelitian ini yaitu remaja berusia 12 – 18 tahun yang tinggal di dalam lingkungan pondok pesantren Assalafi Al Fithrah Surabaya. Berdasarkan perhitungan hasil analisis menggunakan Analisis Regresi Linier Berganda diperoleh skor korelasi sebesar 0.772 dengan signifikansi p=0.000 (p<0.05) yang artinya ada hubungan antara penerimaan diri dan perilaku prososial dengan kebahagiaan. Sementara  itu  diperoleh  skor  sebesar  0.507  dengan  signifikansi  0.000  (p<0.05)  yang artinya terdapat hubungan posistif antara penerimaan diri dan kebahagiaan. Skor korelasi perilaku prososial dengan kebahagiaan sebesar 0.487 dengan signifikansi 0.000 (p<0.05). Hasilnya, semakin tinggi penerimaan diri dan perilaku prososial yang di miliki oleh remaja maka  akan  semakin  tinggi  pula  tingkat  kebahagiaan  yang  di  rasakannya.  Sumbangan efektif dalam penelitian ini    sebesar  0.487  yang  artinya penerimaan diri dan perilaku prososial memiliki pengaruh sebesar 48,7% terhadap kebahagiaan.